Carbon footprint estimate for electromobility in Peru - Sanchez Agurto, Yoner Alejo (2024)
Transportation is the sector with the highest Greenhouse Gasses (GHG) emissions in Peru, and it is almost completely dependent on fossil energy resources. For the present analysis, we take into account carbon emissions during the production of electricity which may serve as a basis for understanding the carbon footprint (CF) of the alternatives that may be derived from the use of electrical vehicles. Based on the estimated values of emissions according to the type of electricity generation source (renewable or thermal), we have created scenarios to calculate emissions under the condition of electromobility. The CF of the combustion vehicle is 180 gCO2eq/pas-km, while the CF of electric vehicles with renewable energy, national electricity and fossil electricity are 12, 89 and 140 gCO2eq/pas-km respectively. The reduction of CO2 emissions eq. with renewable electrical energy is 93%, while 22% with thermal electrical energy; with respect to the current energy source: gasoline. In this work we also aim to numerically show how the use of renewable electrical energy could make transport more sustainable due to the overall reduction of CO2 emissions.